Methods of Piling Work on Long Span Bridges: A Reviev - Apis Indica Adam; Mulia Pamadi (LEADER: Civil Engineering and Architecture Journal, 2023)
Building construction such as bridges, and flyovers. are constructions that need by the public. The selection of the foundation must be done carefully so that it loads above it. Pile planning is one of the solutions in choosing the right foundation. The simple, and relatively inexpensive working method makes the use of the pile method much in demand by planners in various parts of the world. Testing the bearing capacity of the pile is one of the pile work items. where this can ensure quality and quantity in the implementation of the work of this piling method.